Why so few acting whistleblowers? Impacts of institutional anticorruption. Issue 2 (29th April 2019) - Su, Su
Abstract : Despite strong whistleblowing intention, very few truly act to blow the whistle. Building on a random sample of local citizens with citywide anticorruption performance indicators, this study investigated the linkages between institutional anticorruption and citizens' whistleblowing acts, both directly and indirectly via situational settings (i.e., corruption incidence and corruptive climate). The findings confirmed the impacts of varying anticorruption practices and detected both direct and indirect trajectories. More judicial convictions against senior officials directly reduced citizens' subsequent whistleblowing acts, but also indirectly invited more as they signaled more ensuing corruption incidence, with overall effects toward reduced whistleblowing. More citywide public whistleblowing incentivized more individual whistleblowing subsequently; yet, such effects were canceled out as such practices also deterred ensuing corruption incidence and indirectly reduced citizens' acts. The total effects explained why there were so few acting whistleblowers. The study concludes with discussion of research findings and potential policy implications.